Guru PAK Memiliki Kepribadian Yang Arif - Sanny Hornovalyta Sinaga; Dorlan Naibaho (CV. KAMPUS AKADEMIK PUBLISING, 2023)
A wise personality is one of the most important characteristics for a teacher in an educational context. This research aims to dig deeper into how a wise personality influences the quality of teaching and teacher interactions with students. The research methods used were literature studies, interviews with experienced teachers, and observations in the school environment. The research results show that teachers who have wise personalities tend to be better able to understand students' needs, manage the class well, and foster harmonious relationships in the teaching and learning process. They are also able to be good examples for students in terms of morals and ethics